Fatty acids and small organic compounds bind to mineralo-organic nanoparticles derived from human body fluids as revealed by metabolomic analysis. Issue 10 (28th January 2016) - Martel, Jan; Wu, Cheng-Yeu; Hung, Cheng-Yu; Wong, Tsui-Yin; Cheng, Ann-Joy; Cheng, Mei-Ling; Shiao, Ming-Shi; Young, John D.
Abstract : Metabolomic analysis reveals the organic corona of biological and synthetic nanoparticles. Abstract : Nanoparticles entering the human body instantly become coated with a "protein corona" that influences the effects and distribution of the particles in vivo . Yet, whether nanoparticles may bind to other organic compounds remains unclear. Here we use an untargeted metabolomic approach based on ultra-performance liquid chromatography and quadruple time-of-flight mass spectrometry to identify the organic compounds that bind to mineral nanoparticles formed in human body fluids (serum, plasma, saliva, and urine). A wide range of organic compounds is identified, including fatty acids, glycerophospholipids, amino acids, sugars, and amides. Our results reveal that, in addition to the proteins identified previously, nanoparticles harbor an "organic corona" containing several fatty acids which may affect particle-cell interactions in vivo . This study provides a platform to study the organic corona of biological and synthetic nanoparticles found in the human body.